Perspectives of policymakers and health care managers on the retention of health workers in rural and remote settings in Nigeria. (13th April 2021) - Okoroafor, S C; Ongom, M; Mohammed, B; Salihu, D; Ahmat, A; Osubor, M; Nyoni, J; Alemu, W
Abstract: Background: Health workers are indispensable to service delivery especially in rural and remote communities where the burden of disease is high. Nigeria faces numerous human resources for health challenges, health workers are reluctant to take up rural postings, and the government is struggling to implement planned interventions due to staff shortages. This study explored the perspectives of policymakers and primary health care (PHC) managers on factors that hinder health workers from staying in rural and remote areas and strategies for improving retention. Methods: We interviewed purposively selected 10 policymakers and 20 PHC managers in Bauchi and Cross River States, Nigeria. Results: Respondents identified a lack of basic social amenities, the poor state of infrastructure, poor working conditions, remuneration and the barrier to career advancement as factors that impede health workers from taking up rural postings. Strategies for improving retention include enforcing bonding; paying salaries promptly, increase in rural allowances and prioritizing health workers in rural and remote areas for capacity building. Conclusion: The results of the study indicate the importance of applying context-specific strategies aimed at ensuring the availability of social amenities such as roads, water, electricity, telecommunication, security, the status of infrastructure, working conditions and remunerations.